2022
DOI: 10.1111/psyg.12848
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, psychological and social factors associated with older adults' mobility: a scoping review of self‐report and performance‐based measures

Abstract: Although many factors have been associated with mobility among older adults, there is paucity of research that explores the complexity of factors that influence mobility. This review aims to synthesise the available evidence for factors comprising the cognitive, psychological, and social mobility determinants and their associations with mobility self‐reported and performance‐based outcomes in older adults (60 years). We followed Arksey and O′Malley's five stages of a scoping review and searched PubMed, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 223 publications
0
4
0
Order By: Relevance
“…Nevertheless, studies that explore the underlying mechanism (mediators) between self-reported and capacity-based mobility outcomes are scarce. To the best of our knowledge, this study is the first to examine the relationship between several self-reported (LEFS, Mänty Preclinical Limitation Scale, LSQ) and capacity-based mobility (SPPB, 6MWT, 10mWT) outcomes in a developing context while exploring the mediating factors chosen from comprehensive mobility determinants ( Kalu et al, 2022a , 2022b , 2023 ). We found the correlation between self-reported (LEFS and Mänty Preclinical Limitation scale) and capacity-based (SPPB and 6MWT) mobility measures ranged from poor to fair, in the expected direction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies that explore the underlying mechanism (mediators) between self-reported and capacity-based mobility outcomes are scarce. To the best of our knowledge, this study is the first to examine the relationship between several self-reported (LEFS, Mänty Preclinical Limitation Scale, LSQ) and capacity-based mobility (SPPB, 6MWT, 10mWT) outcomes in a developing context while exploring the mediating factors chosen from comprehensive mobility determinants ( Kalu et al, 2022a , 2022b , 2023 ). We found the correlation between self-reported (LEFS and Mänty Preclinical Limitation scale) and capacity-based (SPPB and 6MWT) mobility measures ranged from poor to fair, in the expected direction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be predicted that age-related mobility limitations will increase the burden on social, economic, and healthcare systems [ 2 , 4 ]. Most importantly, studies on older adults’ mobility have been biased towards the biophysical factors, yet sociodemographic determinant is a significant factor in access to health and healthy ageing [ 9 ]. This study will quantify and synthesise the various sociodemographic determinants of mobility in older adults as available in the literature so far and proffer recommendations on the critical directions for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Webber and colleagues have conceptualised a comprehensive older adults’ mobility model including cognitive, environmental, financial, personal, physical, psychological, and social factors [ 2 ]. However, biophysical, and psycho-cognitive aspects of older adults’ mobility are more frequently researched, creating a literature gap on the implications of the sociodemographic factors [ 9 ]. Exploring the influences of demographic and socioeconomic factors may further our understanding of the risks of mobility limitation in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation